A BRIEF REVIEW ON PERIODONTAL DISEASES - Biswas, Raja; Dubey, Chetan Kumar; Singh, Surya Pratap; Khinchi, M. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Periodontal disease is a chronic inflammatory disease of the gum and tissues that surround and support the teeth. Periodontal disease is caused by bacteria in dental plaque, the sticky substance that forms on your teeth a couple of hours after you have brushed. Interestingly, it is your body’s response to the bacterial infection that causes most of the problems. In an effort to eliminate the bacteria, the cells of your immune system release substances that cause inflammation and destruction of the gums, periodontal ligament or alveolar bone. This leads to swollen, bleeding gums, signs of gingivitis (the earliest stage of periodontal disease), and loosening of the teeth, a sign of severe periodontitis (the advanced stage of disease). The main goal of treatment is to control the infection. The number and types of treatment will vary, depending on the extent of the gum disease.